2013
DOI: 10.4103/1947-2714.107537
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal birth after cesarean section

Abstract: Background:The rate of primary cesarean section (CS) is on the rise. More and more women report with a history of a previous CS. A trial of vaginal delivery can save these women from the risk of repeat CS.Aims:The study was conducted to assess the safety and success rate of vaginal birth after CS (VBAC) in selected cases of one previous lower segment CS (LSCS).Materials and Methods:The prospective observational study was carried out in a tertiary care teaching hospital over a period of two years. One hundred p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
40
2
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 20 publications
6
40
2
8
Order By: Relevance
“…если одни предлагают избирательный подход к выбору пациенток с рубцом на матке, родоразрешение которых будет проводиться через естественные родо-вые пути, то другие не исключают возможности оценки состоятельности рубца в интранаталь-ном периоде у всех пациенток. Третьи занима-ют промежуточную позицию [11]. Основная проблема для консервативного родоразреше-ния беременных с рубцом на матке заключает-ся в достоверном определении состоятельности рубца [1,12].…”
unclassified
See 3 more Smart Citations
“…если одни предлагают избирательный подход к выбору пациенток с рубцом на матке, родоразрешение которых будет проводиться через естественные родо-вые пути, то другие не исключают возможности оценки состоятельности рубца в интранаталь-ном периоде у всех пациенток. Третьи занима-ют промежуточную позицию [11]. Основная проблема для консервативного родоразреше-ния беременных с рубцом на матке заключает-ся в достоверном определении состоятельности рубца [1,12].…”
unclassified
“…Исследования других авторов от-личаются от данных показателей незначимо, однако большинство из них считает интер-вал времени 2 и более года необходимым для формирования состоятельного рубца [1,6,7,10,12]. Успех влагалищного родоразрешения беременных с рубцом на матке, у которых по-казанием для предыдущего кесарева сечения служило патологическое состояние плода, со-ставляет 68-83 % [11,14]. В случаях когда пре-дыдущее кесарево сечение было выполнено вследствие клинического несоответствия, успех консервативного родоразрешения колеб лется в пределах 25-85 % [1,6,7,11,14].…”
unclassified
See 2 more Smart Citations
“…Once a caesarean always a hospital delivery is the dictum that means that every patient with a previous LSCS should have an institutional delivery. 5 Various studies have suggested that in women with history of previous caesarean section for indication which is non-recurring, a trial of labour has less complications than elective repeat caesarean section.…”
mentioning
confidence: 99%